Filarial lymphedema is characterized by antigen-specific Th1 and th17 proinflammatory responses and a lack of regulatory T cells. - Subash Babu; Sajid Q Bhat; N Pavan Kumar; Angelo B Lipira; Sanath Kumar; C Karthik; V Kumaraswami; Thomas B Nutman (Public Library of Science (PLoS), 2009)
Lymphatic filariasis can be associated with development of serious pathology in the form of lymphedema, hydrocele, and elephantiasis in a subset of infected patients.To elucidate the role of CD4(+) T cell subsets in the development of lymphatic pathology, we examined specific sets of cytokines in individuals with filarial lymphedema in response to parasite antigen (BmA) and compared them with responses from asymptomatic infected individuals. We also examined expression patterns of Toll-like receptors (TLR1-10) and Nod-like receptors (Nod1, Nod2, and NALP3) in response to BmA. BmA induced significantly higher production of Th1-type cytokines-IFN-gamma and TNF-alpha-in patients with lymphedema compared with asymptomatic individuals. Notably, expression of the Th17 family of cytokines-IL-17A, IL-17F, IL-21, and IL-23-was also significantly upregulated by BmA stimulation in lymphedema patients. In contrast, expression of Foxp3, GITR, TGFbeta, and CTLA-4, known to be expressed by regulatory T cells, was significantly impaired in patients with lymphedema. BmA also induced significantly higher expression of TLR2, 4, 7, and 9 as well Nod1 and 2 mRNA in patients with lymphedema compared with asymptomatic controls.Our findings implicate increased Th1/Th17 responses and decreased regulatory T cells as well as regulation of Toll- and Nod-like receptors in pathogenesis of filarial lymphedema.